Exposure to overprotective parenting and psychopathology in extremely low birth weight survivors. (4th August 2017) - Day, K. L.; Dobson, K. G.; Schmidt, L. A.; Ferro, M. A.; Saigal, S.; Boyle, M. H.; Van Lieshout, R. J.
Abstract: Background: Extremely low birth weight (ELBW; <1, 000 g) infants are the most vulnerable babies and are at higher risk for experiencing overprotective (i.e., controlling and intrusive) parenting, which is hypothesized to contribute to the risk for mental disorders. Despite the increased risk for anxiety disorders and decreased risk for alcohol or substance use disorders seen in ELBW survivors, no research has examined the impact of parenting. This study investigated if overprotective parenting mediates links between ELBW birth status and psychiatric disorders in adulthood. Study design: Participants included ELBW survivors born in 1977–1982 and matched normal birth weight (≥2, 500 g) control participants (ELBW n = 81; normal birth weight n = 87) prospectively followed in Ontario, Canada. These individuals retrospectively reported on whether either of their parents was overprotective using the Parental Bonding Instrument. Presence of a current anxiety disorder and of current alcohol or substance use disorders was assessed using the Mini International Neuropsychiatric Interview at age 29–36 years. Results: Path analysis showed that overprotective parenting was a significant mediator of the association between ELBW status and risk for an anxiety disorder in adulthood and the risk for an alcohol or substance use disorder in adulthood in ELBW survivors. Overprotective parenting accounted for 53% of the association between ELBW status and the risk for an anxiety disorder in adulthood and 26% of the association between ELBW status and alcohol or substance use disorders. Conclusions: Overprotective parenting accounted for a substantial proportion of the increased risk for anxiety and alcohol or substance use disorders in adulthood in ELBW survivors. Despite their perceived vulnerabilities, it is important that the parents of ELBW survivors be supported in their attempts to facilitate their children's pursuit of independence during childhood and beyond.